Benefits of a brief psychological intervention targeting fear of cancer recurrence in people at high risk of developing another melanoma: 12‐month follow‐up results of a randomized controlled trial. (25th July 2019) - Dieng, M.; Morton, R.L.; Costa, D.S.J.; Butow, P.N.; Menzies, S.W.; Lo, S.; Mann, G.J.; Cust, A.E.; Kasparian, N.A.
Summary: Background: People with melanoma want and need effective interventions for living with fear of cancer recurrence (FCR). Objectives: This study reports the 12‐month outcomes of a brief, psychological intervention designed to reduce FCR in people at high risk of developing another primary melanoma compared with usual care. Methods: In this two‐arm randomized controlled trial, adults previously diagnosed with stage 0, I or II melanoma were randomly allocated to the intervention ( n = 80) or control (usual care) arm ( n = 84). The trial was registered with the Australian and New Zealand Clinical Trials Registry on 19 March 2013 (registration: ACTRN12613000304730). The intervention comprised a 76‐page psychoeducational resource and three individually tailored, telephone‐based sessions with a psychologist, scheduled at specific time points around participants' dermatological appointments. The primary outcome was the level of self‐reported fear of new or recurrent melanoma assessed at 12 months postintervention using the severity subscale of the Fear of Cancer Recurrence Inventory. Results: Compared with the control arm, the intervention group reported significantly lower FCR at 12 months postintervention; the between‐group mean difference was −1·41 for FCR severity [95% confidence interval (CI) −2·6 to −0·2; P  = 0·02] and −1·32 for FCR triggers (95% CI −2·6 to −0·02; P  = 0·04). The odds ratio for FCR severity scores ≥13 (54% intervention, 63% control) was 0·59 (95% CI 0·30–1·14, P  = 0·12). There were no differences between groups in secondary outcomes, such as anxiety, depression or health‐related quality of life. Conclusions: The previously reported 6‐month benefits of this brief, patient‐centred psychological intervention in reducing FCR were found to continue 12 months postintervention, with no known adverse effects, supporting implementation as part of routine melanoma care. Abstract : What's already known about this topic? People treated for early‐stage melanoma are at 5–10 times greater risk of developing new primary disease relative to people without a history of melanoma. As a consequence, people who have had melanoma often experience fear of cancer recurrence (FCR) or progression. What does this study add? In this randomized controlled trial, participants who received a brief, multifaceted, patient‐centred psychological intervention reported significantly lower FCR at 12‐months postintervention compared with those in the control arm. The intervention had no known adverse effects and its benefits persisted long after the last psychology session, supporting implementation as part of routine melanoma care. Respond to this article Linked Editorial: Thompson and Cockayne. Br J Dermatol 2020; 182 :821–822.